Chemoselective N-acylation of indoles using thioesters as acyl source - Du, Tianri; Wei, Xiangmu; Xu, Honghong; Zhang, Xin; Fang, Ruiru; Yuan, Zheng; Liang, Zhi; Li, Yahui (Beilstein Journal of Organic Chemistry, 2022)
The selective acylation of indoles often requires sensitive and reactive acyl chloride derivatives. Here, we report a mild, efficient, functional group tolerant, and highly chemoselective N-acylation of indoles using thioesters as a stable acyl source. A series of indoleamides have been obtained with moderate to good yields. In addition, heterocycles, such as carbazole, can also be used as nucleophiles in this reaction.
Keywords: indole; N-acylation; nucleophilic substitution; thioesters

(untitled) - Lancianesi, S.; Palmieri, A.; Petrini, M. (Chem. Rev., 2014)

(untitled) - Shen, T. Y.; Windholz, T. B.; Rosegay, A.; Witzel, B. E.; Wilson, A. N.; Willett, J. D.; Holtz, W. J.; Ellis, R. L.; Matzuk, A. R.; Lucas, S.; Stammer, C. H.; Holly, F. W.; et al. (J. Am. Chem. Soc., 1963)

(untitled) - Yang, Y.; Duan, X.-H.; Deng, J.-Y.; Jin, B.; Jia, H.-M.; Liu, B.-L. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Fang, W.; Deng, Q.; Xu, M.; Tu, T. (Org. Lett., 2013)

(untitled) - Ottoni, O.; Cruz, R.; Alves, R. (Tetrahedron, 1998)

(untitled) - Dhanoa, D. S.; Bagley, S. W.; Chang, R. S. L.; Lotti, V. J.; Chen, T. B.; Kivlighn, S. D.; Zingaro, G. J.; Siegl, P. K. S.; Patchett, A. A.; Greenlee, W. J. (J. Med. Chem., 1993)

(untitled) - Welstead, W. J., Jr; Stauffer, H. F., Jr; Sancilio, L. F. (J. Med. Chem., 1974)

(untitled) - Zeng, J.; Zhang, Z.; Zhu, Q.; Jiang, Z.; Zhong, G. (Molecules, 2020)

(untitled) - Umehara, A.; Ueda, H.; Tokuyama, H. (J. Org. Chem., 2016)

(untitled) - Zhou, X.-Y.; Chen, X. (Synthesis, 2019)

(untitled) - Kikugawa, Y. (Synthesis, 1981)

The chemistry of indoles - Sundberg, R. J. (Ketones, aldehydes, and carboxylic acids derived from indole, 1970)

(untitled) - Maki, B. E.; Scheidt, K. A. (Org. Lett., 2009)

(untitled) - Heller, S. T.; Schultz, E. E.; Sarpong, R. (Angew. Chem., Int. Ed., 2012)

(untitled) - Ta, L.; Sundén, H. (Chem. Commun., 2018)

(untitled) - Wang, M.; Dai, Z.; Jiang, X. (Nat. Commun., 2019)

(untitled) - Li, Y.; Bao, G.; Wu, X.-F. (Chem. Sci., 2020)

(untitled) - Tian, Q.; Xu, S.; Zhang, C.; Liu, X.; Wu, X.; Li, Y. (J. Org. Chem., 2021)

(untitled) - Hardee, D. J.; Kovalchuke, L.; Lambert, T. H. (J. Am. Chem. Soc., 2010)

(untitled) - Laha, J. K.; Kaur Hunjan, M.; Hegde, S.; Gupta, A. (Org. Lett., 2020)

(untitled) - Jiang, Y.-Y.; Liu, T.-T.; Zhang, R.-X.; Xu, Z.-Y.; Sun, X.; Bi, S. (J. Org. Chem., 2018)